2022
DOI: 10.1007/s00520-022-07074-7
|View full text |Cite
|
Sign up to set email alerts
|

Financial difficulties in breast cancer survivors with and without migration background in Germany—results from the prospective multicentre cohort study BRENDA II

Abstract: Purpose We aimed to explore the trajectory of financial difficulties among breast cancer survivors in the German health system and its association with migration background. Methods In a multicentre prospective study, breast cancer survivors were approached four times (before surgery, before and after adjuvant therapy, five years after surgery) and asked about their migration history and financial difficulties. Migrants were defined as born/r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Multiple studies have reported FH and distress among BCS in developed countries [13,[16][17][18][19][20][21]. However, there is very limited research reported in low-and middle-income countries (LMICs) [22].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported FH and distress among BCS in developed countries [13,[16][17][18][19][20][21]. However, there is very limited research reported in low-and middle-income countries (LMICs) [22].…”
Section: Introductionmentioning
confidence: 99%
“…No conclusive information is available on whether participation in psycho-social support services varies based on the migration background of the patients in Germany (Singer et al 2022 ; Zeissig et al 2015 ). However, patients with cancer and migration background are considered to be more likely to have higher psycho-social difficulties (Riccetti et al 2022a ; Tibubos et al 2018 ), as well as higher barriers to access supportive care services than non-migrant patients (Riccetti et al 2022a , b ; Riccetti et al 2020 ; Sze et al 2015 ). Linguistically and culturally competent psycho-social support services are not available in every region (Schulz et al 2018 ), often leading to friends and/or relatives acting as translators, with further difficulties and barriers for patients in discussing their need for psycho-social support (Hermes-Moll et al 2022a ).…”
Section: Introductionmentioning
confidence: 99%